The lamentation of children and relatives in the poetry of Mana Saeed Alotaiba - Alketbi, Anouf; Alhashemi, Badeeah (Al-Adab Journal, 2025)
This research examines the prominent poetic purpose in the poems of the Emirati poet Manaa Said Al-Otaiba, which is the elegy for his sons and mother. Through them, the feelings of pain and grief experienced by the poet due to those difficult circumstances are evident, reflected in the atmosphere of the elegy and its poetic vocabulary and structures. The poet employed expressions and techniques saturated with his feelings and emotions towards the deceased. For Al-Otaiba’s elegiac poem, its general character is unified. It begins with the title of the poem in which the poet declares the name of the deceased, then he starts by stating his relationship with him, and expressing feelings of sadness and grief. Then, he describes the virtues and good deeds of the deceased, ending the poem by submitting to God’s decree, and praying for mercy and forgiveness for the deceased, and for patience and solace for his family, seeking reward from God. What is notable in the poet’s experience is that he has published several of his elegies interactively with readers, through posting them on his social media platforms. This allows the recipient to directly interact with the sad content, and to feel those sincere and touching emotions when reading them. The research is divided after the introduction into three axes. The first is devoted to discussing the purpose of elegy in Arabic poetry and its evolution through different eras. The second is to introduce the poet and his literary productions. As for the third, titled "Elegy in the Poetry of Manaa Said Al-Otaiba," it included the applied study of selected elegies, and the study concluded with a number of results and recommendations. In order to understand the objective and artistic characteristics in the selected poems, the study adopted the descriptive analytical approach.